Posttraumatic Stress Symptoms, Quality of Life, and Stress Burden in Caregivers of Patients With Severe Mental Illness: An Underestimated Health Concern - Rady, Ahmed; Mouloukheya, Tarek; Gamal, Eman (Frontiers in Psychiatry, 2021)
Introduction Care givers of patients with severe mental disorders are subject to heavy stress burden that shows up through various heterogenous psychiatric symptoms that may mimic PTSD with consecutive negative impact on inter-personal relations and work performance Objectives to assess the prevalence of PTSD symptoms, quality of life and stress burden among caregivers of patients with severe mental illness Subjects and Methods 70 care givers of sevely mentally ill patients compred to control 70 care givers of patients with chronic debilitating medical illness. Both groups were recruited from university hospital outpatient facilities. Severe mental illness was defined by Global assessment of function GAF score less than 50 and duration of illness exceeding 2 years. Both groups were subject to Zarit burden interview ZBI, quality of life questionnaire PCASEE and finally, post traumatic stress diagnostic scale PDS to assess PTSD symptoms Results As for results of posttraumatic diagnostic scale PDS: caregivers of patients with severe physical illness didn’t show posttraumatic stress symptoms compared to 37.14% (n=26) of caregivers of patients with severe mental illness had posttraumatic stress symptoms , 15.17% (n=11) of caregivers fulfilled PTSD diagnosis according to DSM V. Caregivers of patients with severe mental illness had higher stress burden and less quality of life than caregivers of patients with severe physical illness (p<0.05) Conclusions Stress burden among care givers of patients with severe mental illness is high and may manifest itself through symptoms that mimic post traumatic stress disorder. This highlights the importance to provide psychological support and assessment to care givers of patients with sever mental illness